Aggressive Video Games Are Not a Risk Factor for Mental Health Problems in Youth: A Longitudinal Study - Ferguson, Christopher J; Wang, C K John (Cyberpsychology, behavior and social networking, 2021)
Recent preregistered studies and analyses have suggested that links between aggressive video games (AVGs) and aggression-related outcomes may have been exaggerated in previous literature. However, concerns about AVGs remain. Although the impact of aggressive games on aggressive behaviors has been the subject of approximately a dozen preregistered studies, the potential impact of aggressive games on the player's mental health symptoms has not been the subject of similar preregistered analyses. In the current study, a sample of more than 3000 youth from Singapore were examined by using preregistered analyses to determine whether early exposure to aggressive games was predictive of anxiety, depression, somatic symptoms, or attention deficit hyperactivity disorder 2 years later. Analyses suggested that exposure to AVGs is not a risk factor for later mental health symptoms.